Perfumers at Work - Norda Essential Oil and Chemical Company (1950)
View of perfumers at work preparing and compounding test samples at the Norda Company plant in Boonton, New Jersey.
Keywords: Norda Essential Oil and Chemical Company; Essences and essential oils industry; Perfumes industry; Employees; Research, Industrial--Laboratories